Evidence for Brassinosteroid-Mediated PAT During Germination of Spathoglottis plicata (Orchidaceae) - Novak, Stacey; Kalbakji, Nataly; Upthegrove, Kylie; Neher, Wesley; Jones, Jay; de León, Jazmin (Frontiers in Plant Science, 2018)
The significance of brassinosteroids (BRs) in shoot growth and their interdependence with auxin has been demonstrated in many plant systems, but comparable studies have not been carried out in orchids. Furthermore, the mechanism for this cross-talk is not entirely understood. Studies on root systems suggest that BRs promote F-actin formation through de-bundling, which mediates PIN-FORMED (PIN) polarity and helps to facilitate auxin flow. In this work, two polar auxin transport (PAT)-dependent events, shoot growth and hair formation, were studied using germinating orchid seed under culture conditions. The degree to which BRs rescued developing seedlings from the impact of actin-bundling agents was evaluated based upon growth responses. A secondary aim of this work was to evaluate the role of BRs in embryo development, since the mature orchid seed is developmentally equivalent to a mid-globular stage of embryogenesis. This study demonstrated the following: 1) Auxin and BRs work together in an interdependent manner to promote optimal protocorm elongation. 2) epibrassinolide (eBL) alleviated the repression in shoot growth, caused by actin-bundling agents, with moderate recovery in leaf development, suggesting additional complexities for PAT and auxin signaling in leaf growth. 3) Shoot formation was repressed in seed embryos under anomalous BR levels, while eBL application elicited positive growth responses in young protocorms. 4) Increased eBL levels inhibited formation of protocorm hairs, whereas the reduction in BR biosynthesis promoted hair initiation, altered hair patterning, and prevented outgrowth of auxin-stimulated hairs. Results from this study also indicated that BRs may enhance orchid protocorm elongation by regulating auxin transport through an F-actin-mediated mechanism. This study clearly revealed that eBL regulates protocorm hair formation through a repressive mechanism, and suggests that eBL may direct PAT to help facilitate hair outgrowth.